Pandangan Islam Terhadap Etika Dakwah Islam Dalam Pembubaran Pengajian Ustadz Syafiq Riza Basalamah Oleh GP Ansor Dan Banser Di Surabaya - Arif Rahman Agustian; Siti Rabi'ah Aladawiyah (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
The dissolution of religious study gatherings is a socio-religious phenomenon that has sparked debate among Muslims, particularly when associated with the principles of religious freedom, the ethics of da’wah, and efforts to maintain social harmony. One case that has attracted public attention is the disbandment of a religious gathering led by Ustadz Syafiq Riza Basalamah in Surabaya. This incident has generated pros and cons between those who view the dissolution as a violation of the freedom to preach and those who consider it a preventive measure to maintain order and unity within the Muslim community. This study aims to analyze the Islamic perspective on the dissolution of the gathering using a qualitative approach through library research. The primary data sources include the Qur’an, particularly Surah At-Taubah verse 107 concerning the event of Masjid Dhirar, the hadith of Prophet Muhammad (peace be upon him), the book Lubāb an-Nuqūl fī Asbāb an-Nuzūl by Jalaluddin As-Suyuthi, and contemporary scholarly literature relevant to the ethics of da’wah and intra-Muslim tolerance. The findings indicate that Islam fundamentally upholds the freedom of da’wah and religious assemblies as part of religious rights. However, Islam also sets ethical boundaries, emphasizing that religious activities must not be used as a means to create harm, division, or social conflict. The dissolution of a religious gathering can only be justified when there is clear evidence of elements that threaten unity and must be carried out through wise, dialogical, and maslahat-oriented mechanisms. Therefore, this study underscores the importance of applying Islamic da’wah ethics that prioritize wisdom (hikmah), consultation (musyawarah), and Islamic brotherhood (ukhuwah Islamiyah) in addressing differences within the Muslim community.